Molecular identification and phylogenetic analysis of Chlorella isolates from Indonesia using rbcL gene - Fauziatul FITRIYAH; Yora FARAMITHA; Dini Astika SARI; Irma KRESNAWATY; Tri PANJI; Djoko SANTOSO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2021)
Identifying the newly isolated species is crucial to establishing a reliable algal database with successful commercial applications for different biotechnological applications. Morphological identification does not give sufficient description, especially for tiny unicellular microalgae. The rbcL gene encodes the large unit of ribulose-1, 5-bisphosphate carboxylase /oxygenase (Rubisco) has been widely known for barcoding in plants and developed for microalgae molecular identification. In this study, we examined the local strains of green microalgae from Indonesia using the rbcL partial gene sequence to identify the strains. Green microalgae isolates originated from Yogyakarta, Serayu, Gondol, Ancol, Cilegon, and Teluk Jakarta were cultured in f/2 media and harvested for DNA extraction. The DNA extracted was proceeded to PCR using 1AB_rbcL primer pair to amplify the sequences of rbcL gene with target band located at 582 bp, followed by the sequencing of the PCR product was conducted. Molecular identification of local green microalgae isolates was successfully carried out using primers 1AB_rbcL with a genetic similarity of 99% toward identified species in the NCBI database. Among six isolates, TJ, G, S, C, and A isolates were identified as C. pyrenoidosa. Only CP isolate from Yogyakarta identified as C. sorokiniana. Nannochloropsis gaditana rbcL sequence was selected as an outgroup. The phylogenetic analysis indicated that the five isolates of Chlorella belong to one clade and clearly distinguished from C. sorokiniana isolate from Yogyakarta.